Life-cycle-assessment of cast stone manufacturing: a case study - Mudga, Devanshu; Pagone, Emanuele; Alkhunani, Rayan A.; Salonitis, Konstantinos (Elsevier, 2021)
This research paper aims to perform a “cradle-to-gate” carbon dioxide emissions Life Cycle Assessment (LCA) on cast stone products, i.e. to quantify their accumulated CO2 emissions from the extraction of raw materials to a complete finished product. The collected data is mapped using Energy Value Stream Mapping (EVSM) and Sankey diagrams. Areas of carbon footprint reduction are identified, and transportation, packaging and mold-making recommendations are made. The study was undertaken at a manufacturing facility located in the UK and based on three types of materials.
Keywords: Life Cycle Assessment; Carbon Footprint; Energy Value Stream Mapping; Sankey Diagram